Students’ Perceptions on The Use of Numbered Head Together Technique in Teaching Reading Comprehension - Eva Cristin Sipayung; Marisi Debora (TRANSFORM : Journal of English Language Teaching and Learning, 2023)
The aim of this study was to find out students’ perceptions on the use of Numbered Head Together technique in teaching reading comprehension. The participants of the study were 30 students of Grade VIII SMP N 35 Medan. The data were analyzed by using descriptive qualitative. The data were collected by conducting observation, questionnaire, and interview. The questionnaire was designed based on Likert scale. The result of this study showed that most students gave positive response on the use of Numbered Head Together technique in teaching and learning reading comprehension process. There were only 9 students who gave negative response to the used of Numbered Head Together technique in teaching reading comprehension which could not help them in learning many reasons namely; they felt uncomfortable to learn in group discussion and they felt boring during the teaching and learning process. In short, the used of Numbered Head Together technique in teaching reading comprehension can motivate and attract them to be more enthusiastic in learning reading comprehension.